Analisis Yuridis terhadap Penggunaan Teknologi Blockchain dalam Pengamanan Data Pribadi: Studi Kasus di Indonesia - Kriswandaru, Althea Serafim; Pratiwi, Berliant; Laksito, Joni; Ariani , Widya; Sholikatun, Siti (Universitas Sains dan Teknologi Komputer, 2024)
Protecting personal data has become increasingly critical in the digital era, especially in Indonesia, where data breaches remain a pressing issue. Blockchain technology has emerged as a potential solution due to its decentralization and enhanced security mechanisms. This study aims to analyze the legal aspects of implementing blockchain technology for personal data protection in Indonesia, focusing on its effectiveness and alignment with existing regulations. A qualitative methodology was employed, including case studies in the fintech and healthcare sectors, supported by normative legal analysis. The findings indicate that blockchain significantly improves data security, with companies reporting a notable decrease in data breaches after adoption. Mechanisms such as hashing and decentralization ensure data integrity and reduce unauthorized access. However, regulatory gaps and high implementation costs hinder widespread adoption. The Personal Data Protection Law (UU PDP) in Indonesia does not yet address the unique characteristics of blockchain, creating legal ambiguities. This study highlights the need for regulatory updates and suggests targeted incentives to encourage adoption. The research contributes to theoretical understanding by integrating legal analysis with blockchain implementation and offers practical recommendations for policymakers. Future studies should explore cross-sectoral applications and comparative analyses with countries successfully adopting blockchain.